Penyuluhan, Cek Kesehatan Dan Pengobatan Gratis Di Klinik Kartika Husada - Happy Elda Murdiana; Istri Bartini; Nisa Isneni Hanifa (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
Diabetes Mellitus is a silent killer disease that can cause both macro and microvascular complications. The prevalence of DM in Indonesia is 1.5% of interviews diagnosed with doctors, and in DIY 12.2% of DM patients are not treated and show taking medication or using insulin from all ages in the Yogyakarta area 89.94%. Prolanis is a health service system and a proactive approach that is implemented in an integrated manner that involves participants, health facilities, and BPJS Kesehatan in the framework of health care for BPJS Kesehatan participants who suffer from chronic diseases to achieve optimal quality of life with cost-effective and efficient health services. Community service is carried out at the Kartika Husada Clinic in DM prolanic patients with counseling methods about DM disease and its prognosis and appropriate pharmacological and non-pharmacological therapies. Followed by supporting health tests as a basis for drug administration. The administration of drugs to prolanis patients is carried out by the interactive Information and Education Communication (IEC) method for both the patient and accompanying family. A series of community services carried out to support the BPJS prolanis program which aims to improve the quality of life of patients by controlling blood sugar and regulating lifestyle.